The Analysis of Planting Procedures in Katiga Irrigation Area, Cigandamekar District, Kuningan Regency - Hibban Nataprayoga; Irfan Bachtiar; Rizqy Yusuf Ramdhani; Nurdiyanto Nurdiyanto (Journal of World Science, 2025)
Water Resources Management involves planning, implementing, monitoring, and evaluating the conservation, utilization, and damage control of water resources. Various issues can arise from an insufficient irrigation water supply, particularly during the dry season. Therefore, assessing plant water requirements, irrigation water availability, and planting patterns is crucial. The Katiga irrigation area, covering 1,010 hectares, is actively used for rice cultivation. During the rainy season, the main crops grown by farmers are rice and secondary crops across three growing seasons. This research calculates water availability by determining the 80% discharge (Q80). The results indicate that the available water for the Katiga irrigation area, located in Cigandamekar Sub-District, Kuningan Regency, ranges from 201.20 l/sec to 1,137.55 l/sec, with the highest water requirement being 956.29 l/sec. The recommended planting pattern is 83% rice and 17% secondary crops for the first growing season, 66% rice and 34% secondary crops for the second growing season, and 29% rice and 17% secondary crops for the third growing season, with the additional division of the field into three groups.